Prussian blue functionalized microcapsules for effective removal of cesium in a water environment. Issue 41 (7th April 2016) - Feng, Shanshan; Li, Xiaoda; Ma, Fang; Liu, Renfa; Fu, Guanglei; Xing, Sen; Yue, Xiuli
Abstract : In this work, a novel non-toxic and effective adsorbent, Prussian blue functionalized microcapsules (PB-MCs) was first developed for the highly efficient removal of cesium ions by flotation separation from aqueous solutions. Abstract : In this work, a novel non-toxic and effective adsorbent, Prussian blue functionalized microcapsules (PB-MCs) was first developed for the highly efficient removal of cesium ions by flotation separation from aqueous solutions. The as-developed PB-MCs adsorbent exhibited excellent adsorption efficiency and rapid separation rate of cesium ions from aqueous solutions by floating due to the efficient combination of the advantages of poly(lactic acid) microcapsules (PLA MCs) and Prussian blue nanoparticles (PB NPs). Using different models for equilibrium and kinetic investigation, it was found that the goodness of mathematical fitting of the experimental data for the adsorption isotherms was in the order of Langmuir > Temkin > Freundlich, the kinetic models were in the order of pseudo-second-order > pseudo-first-order. The initial pH and temperature values both affected the adsorption efficiency of cesium ions. The improved adsorption and capacity of PB-MCs can be attributed to the anchoring technology, which prevented the aggregation of the microcapsules and thus increased the effective adsorption surface of the adsorbent. Furthermore, the PB-MCs adsorbent greatly reduced secondary environmental pollution because of the good biosafety of PB and completely biodegradable of PLA. Meanwhile, Prussian blue functionalized microcapsules could save energy consumption as a result of the flotation separation from wastewater after adsorption. Herein, such a functionalized PB-MCs adsorbent shows great potential applications for effective removal of cesium in wastewater treatment.